Proposed interior design scheme of Dobi Lon and Cafe for Dobi Lon Sdn. Bhd. at Lot 1423 Bandar Seri Iskandar, Mukim Bota, Daerah Perak Tengah, Perak Darul Redzuan / Rohana Sadri - Sadri, Rohana (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Architecture is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to Proposed Interior Design Scheme of Dobi Lon and Cafe for Dobi Lon Sdn. Bhd. at Lot 1243, Bandar Seri Iskandar, Mukim Bota Daerah Perak Tengah, Perak Darul Redzuan. Dobi Lon Sdn. Bhd is currently operated at Persiaran Dataran 2, Bandar Seri Iskandar. The client of this project is Mr Meor Bin Safrizal. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself. Before getting the design that is suitable with the client’s needs, some data analysis should be done such as the types of customers to attend the shop and types of services that offered. The study was performed including site selection studies, interview studies, observation, three study cases and research with a questionnaire. Research and data collection process will be analyzed and applied in the design process to design a comfortable and attractive addition to creating a new image with a touch of style and image of its own. This project proposed based on their need that is a cafe This is the starting of their business in food, before this the company only known in laundry industry. To complete the requirement of this project, interview with Mr Meor and his workers, research in internet, and observation are been done to get all the data that are require, in order to complete the design research. Te site that proposed for this project are the new shop lot at Bandar Seri Iskandar. This proposed Laundry and Cafe is to attract local resident especially UiTM student which nowadays, people are busy with their work and don’t have time to wash their clothes and make daily tasks become easy. This proposal also come up with an idea to design a cafe which be able to attract client. The objective of the project is to provide a new cafe for Dobi Lon Sdn. Bhd. and make development for a new space planning with the best arrangement, so that the customer feels more relax and comfortable when they come and eating in this cafe.